Application of Myofascial Manipulation in the Rehabilitation of Posttraumatic Stiff Elbow - Xu HU; Xia HE; Xu JIN; Baijie XUE; Mingliang JIN; Zhongqi LU; Xiang MOU; Hua YUAN (康复学报)
Objective:To observe the effect of myofascial manipulation on the range of motion (ROM) and the elbow function in patient with posttraumatic stiff elbow.Methods:Forty posttraumatic stiff elbow patients were randomized into intervention group and control group with 20 cases in each group. Both groups received the same conventional rehabilitation treatments program included paraffinotherapy, joint mobilization, static progressive stretch splinting and cold therapy for four weeks; the intervention group received additional myofascial manipulation treatment. The maximum flexion range (ROM-F), the maximum extend range (ROM-E), total range of motion (ROM-T) and Mayo elbow performance scores (MEPS) were measured before and after 4 weeks'treatment.Results:Compared with before treatment, both groups had significant improvement on ROM-F, ROM-E, ROM-T and MEPS (all P<0.01), and the intervention group had significant improvement (P<0.05) than the control group.Conclusion:Myofascial manipulation might be more effective to improve ROM, functional performance of stiff elbow patients.